Si Carancal laban sa ilalim ng dagat Carancal under the sea - Villanueva, Rene O.; Albano, Kora Dandan; Pastor, Boots S. Agbayani (Quezon City Lampara Publishing House, Inc., 2007)
In this story, wherein Carancal goes to the sea to comfort a ferocious creature, the author gives emphasis to the concern for endangered animals and environment as well as love for others.
Text in English and Filipino.
Keywords: Folklore -- Philippines; Heroism in literature